THE GOTHIC CONSTANTS IN THE STORY “ВAD SOOTHSAYER” BY HOMA KUPRIJENKO - Grosevych, І. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article deals the theoretical generalization attributes of gothic poetics especially highlighs the evolution of the image of the witch in World and Ukrainian Literature, analyzed the folkloryzm, the phantasmagoria, the concept of fear, the archetype of way, the implicit naturalistic as dominant features of the gothic organization in the story «Bad Soothsayer» by Homa Kuprijenko.